1985
DOI: 10.1037/0022-006x.53.3.344
|View full text |Cite
|
Sign up to set email alerts
|

Situational approach to the assessment of social competence in children.

Abstract: The present study attempted to generate and evaluate a taxonomy of the situations and tasks most likely to lead deviant children to experience social difficulties. In Study 1, elementary school teachers and clinicians were asked to notice such situations as they occurred. The outcome was a 44-item Taxonomy of Problematic Social Situations for Children. This survey was administered to teachers of 45 socially rejected children and 39 adaptive children. The survey was found to have high internal consistency and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
191
2
28

Year Published

1991
1991
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 247 publications
(226 citation statements)
references
References 17 publications
3
191
2
28
Order By: Relevance
“…A packet of questionnaires, which included the Conflict Tactics Scale (CTS; Straus, 1979), was sent by mail to the fathers who agreed to participate. Approximately 9 weeks after the laboratory visits, researchers visited children's classrooms where teachers rated children's social competence with peers using the Taxonomy of Problematic Social Situations (Dodge, McClaskey, & Feldman, 1985) and classmates provided sociometric data on the target children.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A packet of questionnaires, which included the Conflict Tactics Scale (CTS; Straus, 1979), was sent by mail to the fathers who agreed to participate. Approximately 9 weeks after the laboratory visits, researchers visited children's classrooms where teachers rated children's social competence with peers using the Taxonomy of Problematic Social Situations (Dodge, McClaskey, & Feldman, 1985) and classmates provided sociometric data on the target children.…”
Section: Methodsmentioning
confidence: 99%
“…The two scales were summed to create a measure of peer aggression for each child (␣ ϭ .87). Dodge et al (1985) reported that the test-retest reliability on the entire measure ranges from .57 to .72 for factor scores and is .79 for the total score. The mean, standard deviation, and range of scores in this sample were 34.63, 16.16, and 16 to 75, respectively.…”
Section: Children's Social Competencementioning
confidence: 99%
See 1 more Smart Citation
“…Finally, enacting responses is the manner in which a child actually behaves. The following specific deficits in each of these six steps are related to aggressive behavior: (a) encoding problems involving either hypervigilence to hostile cues or neglecting to take in relevant nonhostile cues (Dodge, Bates, & Pettit, 1990); (b) making hostile (rather than benign) attributions (Dodge, Price, Bachorowski, & Newman, 1990); (c) selecting instrumental (e.g., winning a game) rather than interpersonal (e.g., maintaining a friendship) goals (Slaby & Guerra, 1988); (d) generating fewer behavioral responses overall and a higher proportion of aggressive responses to problems (Asarnow & Callan, 1985); (e) positively evaluating the likely interpersonal and instrumental outcomes of aggression (Crick & Ladd, 1990); and (f) skill in enacting aggressive responses (Dodge, McClaskey, & Feldman, 1985).In most of the SIP literature, these steps have been conceptualized as being discrete processes through which individuals progress, albeit nonconsciously, when they encounter social stimuli. The steps are not presumed to be dependent on one another.…”
mentioning
confidence: 99%
“…Не-зависно о9 узрасLа, ученици са лаком ИО су значајније више ори-јенLисани на заје9ничко решавање ?ро лема (AS=30,97; AS=26,58) и Dрављење ком?ромиса (AS=30,72; AS=23,98) не:о ученици ТР. Пош-Lо не смаLрамо 9а се 9оJијени налази мо:у LумачиLи инLелекLу-алним сDосоJносLима, у скла9у са исLраживањима у DоDулацији 9еце ТР (Dirks et al, 2007;Dodge et al, 1985;Rose-Krasnor, 1997), оJја-шњење веће засLуDљеносLи кооDераLивно:, заје9ничко: начина решавања конфликаLа ученика са ИО не:о ученикаТР ви9имо у моLивационим и сре9инским факLорима. У лиLераLури се ука-зује 9а ко9 осоJа са ИО њихова омеLеносL и Lешкоће Dроузроко-ване сазнајним о:раничењима саме Dо сеJи Dривлаче Dажњу и врло чесLо не:аLивну реакцију и о9Jацивање 9ру:их, шLо 9о9аL-но Dојачава и увеличава њихову DерцеDцију сеJе као 9ру:ачијих (Dagnan & Waring, 2004).…”
Section: дискусија резултатаunclassified